Emirati Arabic : a comprehensive grammar - Leung, Tommi Tsz-Cheung; Ntelitheos, Dimitrios; Al Kaabi, Meera (London ; New York : Routledge, 2021)
"Emirati Arabic: A Comprehensive Grammar offers readers a reference tool for discovering and studying in detail the specific dialect of Arabic spoken in the United Arab Emirates. It covers all major areas of Emirati Arabic grammar, describing in detail its phonological, morphological, syntactic and semantic systems. Each grammatical point is illustrated with numerous examples drawn from native Emirati Arabic speakers and is thoroughly discussed providing both accessible and linguistically informed grammatical description. This book is a useful reference for students of Gulf Arabic and/or Modern Standard Arabic or other Arabic dialects with an interest in the dialect spoken in the UAE, researchers interested in Arabic language and linguistics as well as graduate students and scholars interested in Arabic studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Arabic language -- Dialects -- United Arab Emirates -- Grammar; LANGUAGE ARTS & DISCIPLINES / Journalism